PENGARUH STRES KERJA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PT. INDOMARET KOTA MANNA KABUPATEN BENGKULU SELATAN - Marliza Ade Fitri; Mardhiyah Dwi Ilhami; Herwan MDK (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2022)
This study aims 1) to determine the effect of job stress on employee performance at PT. Indomaret, Manna City, South Bengkulu Regency. 2) To determine the effect of communication on the performance of employees of PT. Indomaret, Manna City, South Bengkulu Regency. 3) to determine the effect of work stress and communication on the performance of employees of PT. Indomaret, Manna City, South Bengkulu Regency. This type of research is a quantitative approach. The method used in this research is descriptive method. The population in this study were all employees of PT. Indomaret Kota Manna, South Bengkulu Regency, totaling 50 employees. samples of 50 employees of PT. Indomaret Kota Manna is part of the Rukis branch, Ibul branch, Kutau branch, Ampera branch and Padang Sialang branch, South Bengkulu Regency. Based on the results of research on the relationship between communication and work stress with employee performance at PT. Indomaret Kota Manna, South Bengkulu Regency, the following conclusions can be drawn: Job stress and communication together have an effect on the performance of PT. Indomaret, Manna City, Bengkulu Regency.